Moderate hyperoxic versus near-physiological oxygen targets during and after coronary artery bypass surgery: a randomised controlled trial. Issue 1 (December 2016) - Smit, Bob; Smulders, Yvo; de Waard, Monique; Boer, Christa; Vonk, Alexander; Veerhoek, Dennis; Kamminga, Suzanne; de Grooth, Harm-Jan; García-Vallejo, Juan; Musters, Rene; Girbes, Armand; Oudemans - van Straaten, Heleen; et al.
Abstract Background The safety of perioperative hyperoxia is currently unclear. Previous studies in patients undergoing coronary artery bypass surgery suggest reduced myocardial damage when avoiding extreme perioperative hyperoxia (>400 mmHg). In this study we investigated whether an oxygenation strategy from moderate hyperoxia to a near-physiological oxygen tension reduces myocardial damage and improves haemodynamics, organ dysfunction and oxidative stress. Methods This was a single-blind, single-centre, open-label, randomised controlled trial in patients undergoing elective coronary artery bypass surgery. Fifty patients were randomised to a partial pressure of oxygen in arterial blood (Pa O2 ) target of 200–220 mmHg during cardiopulmonary bypass and 130–150 mmHg during intensive care unit (ICU) admission (control group) versus lower targets of 130–150 mmHg during cardiopulmonary bypass and 80–100 mmHg at the ICU (conservative group). Primary outcome was myocardial injury (CK-MB and Troponin-T) at ICU admission and 2, 6 and 12 hours thereafter. Results Weighted Pa O2 during cardiopulmonary bypass was 220 mmHg (interquartile range (IQR) 211–233) vs. 157 (151–162) in the control and conservative group, respectively (P  < 0.0001). During ICU admission, weighted Pa O2 was 107 mmHg (86–141) vs. 90 (84–98) (P  = 0.03), respectively. Area under the curve of CK-MB was median 23.5 μg/L/h (IQR 18.4–28.1) vs. 21.5 (15.8–26.6) (P  = 0.35) and 0.30 μg/L/h (0.25–0.44) vs. 0.39 (0.24–0.43) (P  = 0.81) for Troponin-T. Cardiac index, systemic vascular resistance index, creatinine, lactate and F2-isoprostane levels were not different between groups. Conclusions Compared to moderate hyperoxia, a near-physiological oxygen strategy does not reduce myocardial damage in patients undergoing coronary artery bypass surgery. Conservative oxygen administration was not associated with increased lactate levels or hypoxic events. Trial registration Netherlands Trial RegistryNTR4375, registered on 30 January 2014